UPAYA MENINGKATKAN HASIL BELAJAR PKN SISWA DENGAN MENGGUNAKAN MODEL TALKING STICK MATERI SISTEM PEMERINTAHAN PUSAT - Krista Surbakti (JURNAL TEMATIK, 2018)
This study aims to investigate the implementation of Talking Stick model learning  in improving the students learning outcomes on the subject of civics lesson in the central government system. From the results of research conducted by using Talking Sticks in the first cycle of observation results 69% of teachers and 72 student activity observation is good category. Thoroughness of learning outcomes gained 14 people who finished with a percentage of 54% and 12 who did not complete the percentage of 46% with an average value of 62.26, while in the second cycle, the observation of 76.5 teachers and 84 students observation with both categories. The completeness of student learning outcomes obtained 23 who percentage of students who completed at 88.46% and the 3 people who did not complete with the percentage of 11.54% with an average value of the results of the second cycle of 75.15. Based on the research results, it can be concluded that the implementation of Talking Stick model learning on civics lesson in the central government system in class IV private primary school  04948 Gebang improve the students learning outcomes.